Prospect and Challenges of Using Online Mediation in Resolving Domestic Violence - Farahiyah Mohd Nasir, Nur; Ashiqin Zainol , Zinatul; Helmi Md. Said, Muhamad (International Journal of Psychosocial Rehabilitation, 2020)
Purpose of Study: Domestic violence happens when a woman or man regularly hurts his or her spouse physically or verbally such as beats or mentally tortures the other. Meeting face-to-face in the mediation process with the batterer to resolve family disputes may raise the issue of power imbalance, especially when the victim hide the history of violence. This article reviews the challenges of Muslim family disputes in Malaysia resolving the disputes with the history of violence and analyses what online mediation may offer to overcome the said problem.Methodology: Being pure legal research, this paper is doctrinal in its approach.Result: The finding of this research is mediation is not an appropriate mechanism to resolve Muslim family disputes with the history of violence because it will cause more injustice to the victim. Thus, this paper concludes by suggesting online mediation as another alternative to resolve the family disputes.